Case Report: Congenital Erythroleukemia in a Premature Infant with Dysmorphic Features. (July 2016) - Helin, Heidi; van der Walt, Jon; Holder, Muriel; George, Simi
We present a case of pure erythroleukemia, diagnosed at autopsy, in a dysmorphic premature infant who died of multiorgan failure within 24 hours of birth. Dysmorphic features included facial and limb abnormalities with long philtrum, microagnathia, downturned mouth, short neck as well as abnormal and missing nails, missing distal phalanx from the second toe, and overlapping toes. Internal findings included gross hepatomegaly and patchy hemorrhages in the liver, splenomegaly, and cardiomegaly; and subdural, intracerebral, and intraventricular hemorrhages. Histology revealed infiltration of bone marrow, kidney, heart, liver, adrenal, lung, spleen, pancreas, thyroid, testis, thymus, and placenta by pure erythroleukemia. Only 6 cases of congenital erythroleukemia have been previously reported with autopsy findings similar to those of this case. The dysmorphic features, although not fitting any specific syndrome, make this case unique. Congenital erythroleukemia and possible syndromes suggested by the dysmorphic features are discussed.